Capacity Enhancement and Voltage Stability Improvement of Power Transmission Line by Series Compensation - Raihan-Al-Masud, Md.; Islam, Md. Minarul; Hasan, Md. Shahriar; Podder, Prajoy (EAI Endorsed Transactions on Energy Web, 2019)
To install a new infrastructure of a power transmission line is not only costly but also time-consuming, and it also have some harmful impact on our environment and therefore existing transmission infrastructure is important to use effectively. FACTS is a popular solution to utilize this existing power transmission system by using series compensation by means of the series capacitor to enhance the power transmission capacity as well as voltage stability. This paper explores the utilization of series capacitor applying to the power grid of Eastern part of Bangladesh. For doing this we have considered the analytical calculation of 10% to 85% compensation of that power line. As a result, we have observed that the power transfer capacity has been enhanced about 37 times and it also improve the voltage stability, when the compensation ration is 85%. We consider our calculation mathematically and represent the load curve and voltage profile by plotting in Matlab.